UHPSFC/ESI-MS Analysis of Lipids - Lísa, Miroslav; Holčapek, Michal (Methods in molecular biology, 2018)
This new analytical approach for high-throughput and comprehensive lipidomic analysis of biological samples using ultrahigh-performance supercritical fluid chromatography (UHPSFC) with electrospray ionization-mass spectrometry (ESI-MS) is based on lipid class separation using 1.7 μm particle bridged ethylene hybrid silica columns and a gradient of methanol-water-ammonium acetate mixture as a modifier. The method enables a fast separation of 30 nonpolar and polar lipid classes within 6-min analysis time covering six main lipid categories including fatty acyls, glycerolipids, glycerophospholipids, sphingolipids, sterols, and prenols. Individual lipid species within lipid classes are identified based on positive- and negative-ion full scan and tandem mass spectra measured with high mass accuracy and high resolving power. The method is used for the quantitative analysis of lipid species in biological tissues using internal standards for each lipid class. This high-throughput, comprehensive, and accurate UHPSFC/ESI-MS method is suitable for the lipidomic analysis of large sample sets in clinical research.
Keywords: glycerofosfolipidy; sfingolipidy; lipidy; Chromatography, Supercritical Fluid; steroly; Sterols; superkritická fluidní chromatografie; hmotnostní spektrometrie s elektrosprejovou ionizací; metabolomika; Sphingolipids; Pentanols; tandemová hmotnostní spektrometrie; Spectrometry, Mass, Electrospray Ionization; Metabolomics; Glycerophospholipids; Lipids; pentanoly; Tandem Mass Spectrometry